SWOT Analysis of Joint Liability Group - G. , Ramesh Pandi; G. , Thamaraiselvi; R. , Viji; M. , Ramkumar (International Journal of Psychosocial Rehabilitation, 2020)
“All for One and One for All. Based on this quote, when the people are grouped to form a team or union, definitely it makes them feel more powerful and strong as compared with on an individual level. In order to reduce poverty in India, the National Bank for Agriculture and Rural Development (NABARD) introduced a new concept that is called Joint Liability Group (JLG). This scheme helps the small farmers, such as sharecroppers and oral lessees, and also agricultural laborers, by providing institutional credit. The objective of this paper is to discuss the strengths, weaknesses, opportunities, and threats of JLG. The major strength of JLG is group farming, and the weakness of the JLG is that general awareness about JLG among stakeholders is absent. The major opportunities available for JLG is women's empowerment and threats will be faced by the JLG Lack of financial literacy amongst JLG members. It is concluded that bankers should take the necessary steps to create financial literacy among the JLG members. JLG members should make use of their strengths and opportunities in order to reduce and face their weaknesses and threats available outside of the group.